Towards renewable electricity in Europe: An empirical analysis of the determinants of renewable electricity development in the European Union - Ciarán Mac Domhnaill; Lisa Ryan (University College Dublin, UCD School of Economics, 2018)
The twenty-first century must see a decarbonisation of electricity production to mitigate the flow of greenhouse gas emissions into the atmosphere. This paper presents an econometric analysis of the factors that motivate the use of renewable energy in electricity production using panel data from EU Member States during the period 2000-2015. The research extends the literature in this area in several ways. Firstly, the econometric analysis is focused on the electricity sector rather than on the overall primary energy supply, which also includes the diverse heating and transport sectors. In addition, an alternative public policy variable is proposed using the tax and levy component of electricity bills. Furthermore, an alternative econometric approach is employed using a hybrid mixed effects estimator. The results of this analysis are found to be broadly as expected, with mixed fossil fuel price effects; electricity grid interconnection and higher levels of greenhouse gas emissions both motivate the development of renewable electricity. Policy implications are that policy support for fossil fuels should be ceased; electricity grid interconnections should be developed between countries; and furthermore, levies on retail electricity prices to fund RE support schemes are effective at promoting renewable electricity.
Keywords: Q21; Q4; Q41; Q42; Q58; 330